Consumer behavior and insurer plan offering with expanded premium subsidy in U. S. individual health insurance market - Lei, Yu (Frontiers in Public Health, 2025)
As the demand for individual health insurance in the U. S. ebbed and flowed between 2014 and 2024, the supply of such coverage also fluctuated accordingly, based on our descriptive analysis of enrollment data and insurer information. With the enhanced premium subsidy available since 2021, consumers were trading up and purchasing more gold plans and less silver plans. Insurers in turn offered more of the desired plans. Our results also showed that insurers offered a higher percentage of silver plans but a lower percentage of bronze plans than the consumer demanded.